Bacteriocin-Producing Enterococcus faecium LCW 44: A High Potential Probiotic Candidate from Raw Camel Milk - Vimont, Allison; Fernandez, Benoît; Hammami, Riadh; Ababsa, Ahlem; Daba, Hocine; Fliss, Ismaïl (Frontiers in Microbiology, 2017)
Bacterial isolates from raw camel milk were screened for antibacterial activity using the agar diffusion assay. Ten isolates selected for their inhibition of Gram-positive bacteria were identified by 16S sequencing as Enterococcus faecium or durans. An isolate named E. faecium LCW 44 exhibited the broadest antibacterial spectrum with an inhibitory activity against several Gram-positive strains belonging to the genera Clostridium, Listeria, Staphylococcus and Lactobacillus. E. faecium LCW 44 was shown to produce N-formylated enterocins L50A and L50B, as revealed by mass spectrometry and PCR analyses. This isolate did not harbor any of the virulence factors tested and was shown to be sensitive to all tested antibiotics. It showed high resistance to gastric and intestinal conditions (78 ± 4 % survival). Its adhesion index was evaluated at 176 ± 86 and 24 ± 86 on Caco-2 cells and HT-29 cells respectively, and it significantly reduced adhesion of L. monocytogenes by 65 % and 49 % respectively. In Macfarlane broth (simulating the nutrient content of the colon), counts of Listeria monocytogenes were reduced by 2 log10 cycles after 24 h in co-culture with E. faecium LCW 44, compared to the increase of 4 log10 cycles when cultured alone. Comparison with a bacteriocin-non-producing mutant of E. faecium LCW 44 strongly suggests that inhibition of L. monocytogenes was due to bacteriocin production. Altogether, E. faecium LCW 44 thus has potential for use as a probiotic for humans and veterinary medicine.